Short-Term Capital, Economic Transformation, and EU Accession - Lusine Lusinyan; Claudia M. Buch (Deutsche Bundesbank, 2002)
One key focus of the on-going debate on the integration of international financial markets have been measures to lengthen the maturity of foreign debt, as short-term debt is typically considered to be highly volatile. The transition economies of Central and Eastern Europe are one group of countries for which policy lessons seem particularly urgent. Not only have these countries liberalized their capital accounts to a quite substantial degree already, membership in the European Union also implies that remaining controls to the free flow of capital will have to be abolished. This paper assesses the experience of the transition economies with liberalizing short-term capital flows, and it analyzes factors affecting the share of short-term capital. – – Da eine Verschuldung in kurzfristiger Form oft als sehr volatil angesehen wird, betrifft ein wichtiger Aspekt der gegenwärtigen Diskussion über die Integration der internationalen Finanzmärkte die Frage, wie man die Fristigkeit der Auslandsverschuldung verlängern kann. Für die Transformationsländer Zentral- und Osteuropa scheinen politische Lehren in dieser Beziehung besonders wichtig. Diese Länder haben ihren Kapitalverkehr schon zu einem großen Teil liberalisiert und die künftige Mitgliedschaft in der EU verlangt das Ende der noch bestehenden Kontrollen. Dieses Papier betrachtet die Erfahrungen der Transformationsländer bei der Liberalisierung des kurzfristigen Kapitalölverkehrs und analysiert die Faktoren, die den Anteil der kurzfristigen Verschuldung beeinflussen.
Keywords: F21; F23; G21; 330; Short-term debt; economic transformation; EU accession; Internationale Kapitalmobilität; Auslandsverschuldung; EU-Erweiterung; Kapitalmarktliberalisierung; Übergangswirtschaft; Osteuropa; short-term capital flows